2006
DOI: 10.1107/s1600536806003540
|View full text |Cite
|
Sign up to set email alerts
|

2-(4-Hydroxystyryl)-1-methylpyridiniump-toluenesulfonate

Abstract: In the title compound, C14H14NO+·C7H7O3S−, the cation is almost planar and adopts an E configuration. In the crystal structure, the cations and anions are packed as alternate layers parallel to the ac plane. These layers are inter­connected through O—H⋯O, C—H⋯O and C—H⋯π inter­actions, forming a three‐dimensional supramol­ecular network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 13 publications
4
21
0
Order By: Relevance
“…Bond lengths and angles in both cation and anion are in normal ranges (Allen et al, 1987) and are comparable with those observed in a closely related structure (Chantrapromma et al, 2006). The cation is almost planar, as indicated by the dihedral angle between the pyridinium (N1/C7-C11) and benzene (C14-C19) rings of 4.52 (8) [3.46 (8) in Chantrapromma et al, 2006], and exists in an E configuration with respect to the C12 C13 double bond [1.345 (2) Å , cf. 1.323 (3) Å in Chantrapromma et al, 2006].…”
Section: Commentsupporting
confidence: 80%
See 1 more Smart Citation
“…Bond lengths and angles in both cation and anion are in normal ranges (Allen et al, 1987) and are comparable with those observed in a closely related structure (Chantrapromma et al, 2006). The cation is almost planar, as indicated by the dihedral angle between the pyridinium (N1/C7-C11) and benzene (C14-C19) rings of 4.52 (8) [3.46 (8) in Chantrapromma et al, 2006], and exists in an E configuration with respect to the C12 C13 double bond [1.345 (2) Å , cf. 1.323 (3) Å in Chantrapromma et al, 2006].…”
Section: Commentsupporting
confidence: 80%
“…The cation is almost planar, as indicated by the dihedral angle between the pyridinium (N1/C7-C11) and benzene (C14-C19) rings of 4.52 (8) [3.46 (8) in Chantrapromma et al, 2006], and exists in an E configuration with respect to the C12 C13 double bond [1.345 (2) Å , cf. 1.323 (3) Å in Chantrapromma et al, 2006]. The C11-C12-C13-C14 torsion angle is 179.58 17.…”
Section: Commentmentioning
confidence: 99%
“…The cation is almost planar and exists in an E configuration with respect to the C6 C7 double bond [1.322 (2) Å ]. The dihedral angle between the pyridinium and benzene rings is 4.50 (8) ; this compares with 3.46 (8) in 2-(4-hydroxystyryl)-1-methylpyridinium p-toluenesulfonate, (II) (Chan-trapromma, Ruanwas, Jindawong et al, 2006) and 4.52 (8) in 2-(4-hydroxystyryl)-1-methylpyridinium 4-bromobenzenesulfonate, (III) (Chantrapromma, Ruanwas, Fun & Patil, 2006).…”
Section: Commentmentioning
confidence: 85%
“…The most important requirement for non-linear optical (NLO) materials to exhibit second-order NLO properties is for the molecules to be oriented in a non-centrosymmetric environment (Williams 1984). The X-ray crystal structure determination of the title compound, (I), was carried out in order to obtain detailed information of the molecular packing of (I), and to gain more information on the effect of the counteranion on the crystal packing and the NLO properties of similar compounds (Chantrapromma, Ruanwas, Jindawong et al, 2006;Chantrapromma, Ruanwas, Fun & Patil, 2006). However, compound (I) crystallizes in the centrosymmetric space group P2 1 /c and does not exhibit second-order NLO properties.…”
Section: Commentmentioning
confidence: 99%
“…For related literature on nonlinear optical materials, see: Chantrapromma et al (2005Chantrapromma et al ( , 2006; Fun et al (2006) ; ;. For bondlength data, see: Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%